Anxiety during the pandemic in elderly in a disadvantaged population of San Juan de Lurigancho - Cosio Tapia, Agustina (2021)
Objectives: To determine anxiety during the pandemic in the elderly of a disadvantaged population of San Juan de Lurigancho. Materials and methods: This study with the methodological approach of this study was of a descriptive-cross-sectional design. The population consisted of 84 elderly people who were cared for from a disadvantaged population. The technique used was the survey and the measurement instrument was the Generalized Anxiety Disorder Scale (GAD-7), which is made up of 7 items and two dimensions, which are: cognitive-emotional and somatic-tension. Results: According to age, the minimum was 55 and the maximum 96, the mean age being 72.65. Regarding anxiety, moderate anxiety predominates with 39.3% (n = 33), followed by level anxiety in 32.1% (n = 27), without anxiety with 17.9% (n = 15) and severe anxiety in 10.7% (n = 9). In relation to the cognitive-emotional dimension, mild and moderate anxiety had a higher prevalence with 36.9% (n = 31), followed by no anxiety in 16.7% (n = 14) and severe anxiety with 9.5% (n = 8). Regarding the somatic-tension dimension, mild anxiety predominated in 35.7% (n = 30), followed by moderate anxiety with 33.3% (n = 28), without anxiety in 22.6% (n = 19) and severe anxiety with 8.3% (n = 7). Conclusions: Regarding anxiety, moderate anxiety predominated, followed by mild anxiety, without anxiety and severe anxiety. Regarding the dimensions, mild anxiety predominated, followed by moderate, without anxiety and severe.